Effects of exercise intensity and duration on the excess post-exercise oxygen consumption - Laforgia, J.; Withers, R. T.; Gore, C. J. (Journal of Sports Sciences, 2006)
Recovery from a bout of exercise is associated with an elevation in metabolism referred to as the excess post-exercise oxygen consumption (EPOC). A number of investigators in the first half of the last century reported prolonged EPOC durations and that the EPOC was a major component of the thermic effect of activity. It was therefore thought that the EPOC was a major contributor to total daily energy expenditure and hence the maintenance of body mass. Investigations conducted over the last two or three decades have improved the experimental protocols used in the pioneering studies and therefore have more accurately characterized the EPOC. Evidence has accumulated to suggest an exponential relationship between exercise intensity and the magnitude of the EPOC for specific exercise durations. Furthermore, work at exercise intensities =50 - 60% &Vdot;O2max stimulate a linear increase in EPOC as exercise duration increases. The existence of these relationships with resistance exercise at this stage remains unclear because of the limited number of studies and problems with quantification of work intensity for this type of exercise. Although the more recent studies do not support the extended EPOC durations reported by some of the pioneering investigators, it is now apparent that a prolonged EPOC (3 - 24 h) may result from an appropriate exercise stimulus (submaximal: =50 min at =70% &Vdot;O2max; supramaximal: =6 min at =105% &Vdot;O2max). However, even those studies incorporating exercise stimuli resulting in prolonged EPOC durations have identified that the EPOC comprises only 6 - 15% of the net total oxygen cost of the exercise. But this figure may need to be increased when studies utilizing intermittent work bouts are designed to allow the determination of rest interval EPOCs, which should logically contribute to the EPOC determined following the cessation of the last work bout. Notwithstanding the aforementioned, the earlier research optimism regarding an important role for the EPOC in weight loss is generally unfounded. This is further reinforced by acknowledging that the exercise stimuli required to promote a prolonged EPOC are unlikely to be tolerated by non-athletic individuals. The role of exercise in the maintenance of body mass is therefore predominantly mediated via the cumulative effect of the energy expenditure during the actual exercise.